The Islamic Taste in Laws and Regulations Establishment: Case of Gorontalo Province, Indonesia - Abdussamad, Zamroni; Achir, Nuvazria (Law Research Review Quarterly, 2020)
The presence of a local regulation containing religious teachings has recently been challenged in the form of criticism, which considers that the existence of this regulation product is a form of discrimination and is not effectively implemented. The results of the study, Gorontalo Province, dubbed "Serambi Madinah", the majority of the population is Muslim, putting religion as the main thing in the affairs of life. The urgency of the teachings of Islam in the formation of legal products in Gorontalo is based on several things, in addition to being considered a local wisdom, the law instead presents justice, prosperity and prosperity for its people and serves as a benchmark for how to live a national life based on Pancasila without violating the value of tolerance towards other people. Local regulations based on religious teachings also contain solutions to overcoming the problems of poverty, economic, social and cultural areas that originate from the Qur'an where the teachings are for the salvation of humanity from moral damage. Therefore, it is important to present regulations containing the content of Islamic teachings as a form of preventive and repressive measures for all forms of crime and deviant behavior. Islamic teachings are considered important to be the substance, in addition to supporting parents to provide assistance to children's activities, it also supports the government in carrying out its duties and responsibilities in social affairs.